Breaking Bad News: Dynamic Molecular Mechanisms of Wound Response in Plants - Vega-Muñoz, Isaac; Duran-Flores, Dalia; Fernández-Fernández, Álvaro Daniel; Heyman, Jefri; Ritter, Andrés; Stael, Simon (Frontiers in Plant Science, 2020)
Recognition and repair of damaged tissue is an integral part of life. The failure of cells and tissues to appropriately respond to damage can lead to severe dysfunction and disease. Therefore, it is essential that we understand the molecular pathways of wound recognition and response. In this review we aim to provide a broad overview of the molecular mechanisms underlying the fate of damaged cells and damage recognition in plants. Damaged cells release so called damage associated molecular patterns to warn the surrounding tissue. Local signaling through calcium (Ca2+), reactive oxygen species (ROS) and hormones such as jasmonic acid activate defense gene expression and local reinforcement of cell walls to seal off the wound and prevent evaporation and pathogen colonization. Depending on the severity of damage, Ca2+, ROS and electrical signals can also spread throughout the plant to elicit a systemic defense response. Special emphasis is placed on the spatiotemporal dimension in order to obtain a mechanistic understanding of wound signaling in plants.